Analysis of Genetic Variation of the Voltage-gated Sodium Channel Gene Sequence in Aedes albopictus NCBI PopSet 2222555040 Using In Silico RFLP - Putri, Aisyah Fadilah Putri; Fatia, Inayatul; Achyar, Afifatul; Ramadanil, Syahrul; Satria, Rijal; Putri, Dwi Hilda (Microbiotech, 2024)
The aim of this research is to analyze the genetic variation of Aedes albopictus using RFLP in silico.The method used in this research is screening of candidate restriction enzymes that will be used in in silico RFLP using tools on the website http://insilico.ehu.es/restriction/ . This tool will compare the restriction patterns of many DNA sequences tested as well as the restriction enzymes that cut them, and Restriction-Fragment Length Polymorphism (RFLP) in silico or virtual restriction is carried out using tools on the site https://www.benchling.com/. The results of this study are that the Aedes albopictus genome is the largest of any mosquito species sequenced to date, varying from 174 Mb for Anopheles darlingi to 540 Mb and 1,376 Mb for Culex quinquefasciatus and Ae. aegypt. Genome size variation is also observed among different populations of Ae. albopictus. Analysis of 47 geographic isolates from 18 countries showed a 2.5-fold variation in haploid genome weight range from 0.62 pg in a population on Koh Samui (Thailand) to 1.66 pg. Inter- and intraspecific variation in genome size among mosquitoes appears to be caused primarily by changes in the number and organization of DNA repeats. Increased abundance of all classes of DNA repetitive sequences correlated linearly with total genome size.